The relationship between regional homogeneity in resting-state functional magnetic resonance imaging and cognitive function in depressive disorders with migraine - Wensheng Chen; Guojun Xie; Caixia Xu; Jiaquan Liang; Chunguo Zhang (Scientific Reports)
Abstract Patients with depressive disorder with migraine (DDWM) are common, yet the neural mechanisms and brain function changes associated with this comorbidity remain partially understood. This study explores regional homogeneity (ReHo) abnormalities in resting-state functional magnetic resonance imaging (fMRI) and cognitive function in DDWM patients. We recruited 29 patients with DDWM, 34 patients with depressive disorder without migraine (DDWOM), and 43 matched healthy controls (HC). All participants underwent rs-fMRI scans, and imaging data were analyzed using ReHo. Cognitive function was assessed with the Repeatable Battery for the Assessment of Neuropsychological Status. We also employed support vector machine (SVM) analysis to evaluate whether abnormal ReHo values could distinguish DDWM. he DDWM group exhibited significantly lower ReHo values in the left cuneus and left calcarine compared to the DDWOM group. ReHo values in these regions were negatively correlated with pain scores on the Visual Analogue Scale (r = − 0.3628, p = 0.0001; r = − 0.3142, p = 0.001) and positively correlated with the List_Recall score on RBANS (r = 0.260, p = 0.007). SVM analysis indicated that the left cuneus ReHo value could distinguish DDWM from DDWOM with 78.09% accuracy, 87.66% sensitivity, and 74.33% specificity. The left cuneus and left calcarine are potential biomarkers for migraine symptoms in DDWM, with the left cuneus affecting cognitive function related to memory.